Detection of aflatoxin-producing fungi in maize (Bangladesh Veterinarian, 2022)
Maize samples (n = 110) were collected from five different areas of Dinajpur district from July 2018 to July 2019 for the detection of aflatoxin-producing fungi and aflatoxin. Aflatoxin-producing fungi were detected using culture and morphological features, and aflatoxin was detected using Agra Strip total aflatoxin test (20 ppb cut-off). Aspergillus spp. were detected in 56% of fresh and 23.2% of stored maize samples. Aflatoxin-producing fungi were detected in 28% of fresh samples and aflatoxin was detected in 10% of stored samples. Out of 110 maize samples, Aspergillus spp was identified in 38.2%, and aflatoxinproducing fungus was found in 18.2%. The presence of aflatoxin-producing fungus in stored maize increased significantly (P